A differential interplay between the expression of Th1/Th2/Treg related cytokine genes in Teladorsagia circumcincta infected DRB1*1101 carrier lambs - Hassan Musa; Hanrahan James P; Good Barbara; Mulcahy Grace; Sweeney Torres (Veterinary Research, 2011)
Abstract Substantial debate exists on whether the immune response between sheep resistant and susceptible to gastrointestinal nematodes can be differentiated into a Th1 and Th2 phenotype. The present study addresses the hypothesis that variation in resistance to Teladorsagia circumcincta between DRB1*1101 (associated with reduced faecal egg count and worm burden) carriers and non-carriers is due to a differential interplay in the expression of Th1/Th2 and regulatory T (Treg) related cytokine genes. Lambs from each genotype were either slaughtered at day 0 (un-infected control) or infected with 3 × 104 Teladorsagia circumcincta L3 and slaughtered at 3, 7, 21, and 35 days later. Lambs carrying the DRB1*1101 allele had a significantly lower worm burden (P < 0.05) compared to the non-carriers. Abomasal mucosal cytokine gene expression was evaluated by quantitative real-time PCR and comparison made for time and genotype effects. The response generated varied through the course of infection and was affected by genotype. DRB1*1101 carriers had an up-regulated expression of the Th1-related cytokine genes (IL-1β, TNFα, and IFN-γ) at day 3, but this was replaced by an up-regulated expression of Th2-related cytokine genes (IL-10 and IL-13) and Treg-related cytokine genes (IL-2RA-CD25, TGFα, TGFβ, Arg2, MIF and FOXP3) by day 7. Conversely, in the non-carriers these changes in gene expression were delayed until days 7 and 21 post infection (pi), respectively. It is concluded that resistance to Teladorsagia circumcincta in animals carrying the DRB1*1101 allele is influenced by an earlier interplay between Th1, Th2 and T regulatory immune response genes.